A disaster by any other name?: COVID‐19 and support for an All‐Hazards approach. Issue 3 (7th April 2021) - Penta, Samantha; Kendra, James; Marlowe, Valerie; Gill, Kimberly
Abstract: Disasters are among the crises that can test the decision making skill of elected and appointed public officials from planning through response and recovery. The COVID‐19 crisis, a public health emergency rather than one with immediate damage to the built environment, has affected many aspects of community life. Experiences in responding to the pandemic will likely stimulate fresh planning initiatives for public health emergencies. How then should emergency planners approach planning and response tasks? The All‐Hazards approach has been a mainstay of both research and policymaking for over 40 years, but it has come under recent criticism. In this paper, we consider if the All‐Hazards approach to disaster management is still viable. Comparing the management needs that emerged in the pandemic with those of disasters from more familiar hazard agents, we conclude that the All‐Hazards approach is valid and can continue to guide policymakers in their hazard and disaster management activities. RESUMEN: Los desastres se encuentran entre las crisis que pueden poner a prueba la capacidad de toma de decisiones de los funcionarios públicos electos y designados desde la planificación hasta la respuesta y la recuperación. La crisis de COVID‐19, una emergencia de salud pública en lugar de una con daños inmediatos al entorno construido, ha afectado muchos aspectos de la vida comunitaria. Las experiencias en la respuesta a la pandemia probablemente estimularán nuevas iniciativas de planificación para emergencias de salud pública. Entonces, ¿cómo deben abordar los planificadores de emergencias las tareas de planificación y respuesta? El enfoque todos los peligros ha sido un pilar de la investigación y la formulación de políticas durante más de 40 años, pero ha sido objeto de críticas recientes. En este documento, consideramos si el enfoque de todos los peligros para la gestión de desastres sigue siendo viable. Al comparar las necesidades de gestión que surgieron en la pandemia con las de los desastres de agentes de peligro más familiares, llegamos a la conclusión de que el enfoque de todos los peligros es válido y puede seguir guiando a los responsables de la formulación de políticas en sus actividades de gestión de peligros y desastres. 摘要: 在各类危机中，灾害能检验经过选举和任命的公共官员在规划、响应和恢复过程中的决策技能。新冠肺炎（COVID‐19）危机是一场公共卫生紧急事件，不是一次对建成环境造成直接损害的灾害，它已影响了社区生活的多个方面。大流行的响应经验将有可能激励全新的规划倡议，以应对公共卫生紧急事件。应急规划者则应如何处理规划和响应任务？全灾害管理模式（All‐Hazards approach）在过去40年里一直是研究和决策的支柱，但最近却遭到了批判。本文中，我们考量了全灾害管理模式是否仍然有效。通过将大流行的管理需求和"由更熟悉的灾害因素造成的灾害"的管理需求进行比较，我们的结论认为，全灾害管理模式仍然成立，并且能继续指导决策者进行灾害管理活动。